Revision of Digonocryptus Viereck (Hymenoptera: Ichneumonidae: Cryptinae), with twenty six new taxa and cladistic interpretation of two species complexes - Aguiar, Alexandre Pires; Ramos, Adriana C. B. (Zootaxa, 2011)
Digonocryptus Viereck, a large genus of Neotropical Cryptini, is diagnosed, described, and fully revised. Two species complexes are proposed, and cladistically resolved. A total of 45 valid species are recognized, of which 26 are described as new, D. arcaeus, D. archisius, D. atrozyrix, D. banius, D. boraeus, D. caceres, D. campygeus, D. caraguatensis, D. cennitus, D. domius, D. elegans, D. huntus, D. iageus, D. meridensis, D. mettus, D. petrus, D. pitchus, D. rufozyrix, D. sautatus, D. silopoeus, D. sipius, D. siraeus, D. teleborus, D. variabilis, D. yacamus, and D. yunnus. Other valid species are D. annulitarsis (Cameron), D. chiriquensis (Cameron), D. coloratus (Szépligeti), D. crassipes (Brullé), D. denticulatus (Taschenberg), D. diversicolor (Viereck), D. grossipes (Brullé), D. inermis (Szépligeti), D. inflatus (Brullé), D. narratorius (Fabricius), D. niger (Szépligeti), D. propodeator Kasparyan et Ruíz, D. pulchripes (Cameron), D. rufigaster (Szépligeti), D. sutor (Fabricius), D. tarsatus (Cresson), D. thoracicus Kasparyan et Ruíz, D. variegatus (Szépligeti), and D. varipes (Brullé). Four new synonymies are proposed: D. insularis (Ashmead) and D. grenadensis (Ashmead) as junior synonyms for D. narratorius (Fabricius); D. rufithorax (Taschenberg) as junior synonym for D. inflatus (Brullé); and D. femorator Kasparyan et Ruíz as junior synonym for D. variegatus (Szépligeti). A total of 44 new distribution records are registered for all valid species except D. propodeator and D. tarsatus. A taxonomic key for species based on females, habitus and propodeum illustrations, along with photographic illustrations of diagnostic features, are provided for all valid species.